Security of the Internet and the Known Unknowns. (Communications of the ACM, 2012)
The article focuses on Internet vulnerabilities and Internet security. Topics include the regulation of Network Operation Centers (NOCs) on the Internet, Border Gateway Protocol (BGP), and why computer security systems are unable to keep up with the expansion of the Internet. Information is provided on the cost-effective balance between security systems and computer security failures, the impact of Internet vulnerabilities, and comprehensive security monitoring. It is noted that the government could improve Internet security and reliability through basic policies.